Toward application of biocontrol to inhibit wine spoilage yeasts: The use of statistical designs for screening and optimisation - Kuchen, Benjamín (2021)
Spoilage yeasts generate considerable economic losses in the wine industry, and although sulphur dioxide (SO2) is traditionally used for control, its use has become controversial because of its negative effects on health. Biocontrol has emerged as a partial alternative to SO2, and most research has focused on the selection of biocontrol yeasts and/or the mechanisms involved, while little research has been directed to the environmental conditions that make biocontrol effective for application. When there are two or more interacting yeasts, the physicochemical factors that affect their antagonism are many and therefore the application of biocontrol is complex. To reduce SO2, the present study aimed to elucidate biocontrol mechanisms of two yeast interactions and to establish optimal physicochemical conditions for biocontrol of the spoilage yeast during grape must fermentation. Through the use of statistical design, it was possible to find relevant physicochemical factors and optimise them. Wickerhamomyces anomalus “BWa156” developed an active supernatant against Zygosaccharomyces rouxii “BZr6” while supernatant from Metschnikowia pulcherrima “BMp29” was ineffective. In mixed must fermentations, the first interaction (BWa156 vs. BZr6) showed fewer physicochemical factors impacting biocontrol compared to the second interaction (BMp29 vs. BZr6). However, the fewer factors of the first interaction had a stronger effect on the decline in the spoilage population. Validations showed that the optimal conditions for biocontrol with the first interaction could be predicted. Analysis of the results with BWa156 vs. BZr6 and BMp29 vs. BZr6 suggests that the first interaction is a competition that includes a killer toxin, while the second interaction involves competition for iron resources. Response surface methodology (RSM) allowed a reduction in the number of experiments and permitted to find the optimal biocontrol conditions (SO2: 0 mg mL-1; pH: 3.7; Reducing sugars: 23 °Brix) for the interaction between BWa156 and BZr6.